Artificial skin for sweating guarded hotplates and manikins based on weft knitted fabrics. Issue 4 (February 2019) - Mark, Annette; Psikuta, Agnes; Bauer, Boris; Rossi, René Michel; Gresser, Götz Theodor
Measurement devices such as sweating manikins, cylinders or hotplates are used for testing thermal and moisture transfer properties of clothing or textiles. A critical feature of these measurement devices is the design of the outer covering fabric that tightly enfolds the device like a skin. The artificial skin principally has to match individual requirements because the different sweating devices have different sweating systems and surface compositions. In this study knitted fabrics with different fiber and yarn types are proposed to be used as an artificial skin. Thermal and moisture properties of the fabrics were measured to obtain skin-like characteristics and a mathematical model for the quantification of thermal and moisture-management properties based on geometrical characteristics was developed. The results show that the thermal and moisture-management properties of the fabrics do not only depend on the fiber properties but also relevantly on their geometrical properties such as thickness, diameter and number of stitch pores. For example, thermal resistance is significantly affected by the stitch pore diameter, and evaporative resistance by the fabric thickness. Furthermore, water content and drying speed are determined by the capillary structure, and therefore, are more influenced by yarn and fabric structure parameters, whereas contact angle and wettability are more influenced by the fiber type. In conclusion, the tested fabrics satisfy all the requirements to match the anatomical properties of the human skin; however, two fabric types, PES_19f30_SET and PES_28f48_GL, exhibited superior characteristics suitable for application as artificial skin on measurement devices.